Driving Errors That Predict On-Road Outcomes in Adults With Multiple Sclerosis. (July 2017) - Krasniuk, Sarah; Classen, Sherrilene; Morrow, Sarah A.; Monahan, Miriam; Danter, Tim; Rosehart, Heather; He, Wenqing
Driving errors that predict on-road outcomes for persons with multiple sclerosis (PwMS) are not well studied. The objective of this study was to determine whether adjustment-to-stimuli and gap acceptance errors significantly predict passing/failing a standardized on-road assessment of PwMS. Thirty-seven participants completed visual ability and visual attention assessments, and participated in an on-road assessment, where seven types of driving errors and pass/fail outcomes were determined. Adjustment-to-stimuli (No.) and gap acceptance errors (commit/did not commit) significantly predicted passing/failing the on-road assessment, with an area under the curve of 91.6% ( p < .0001). With no gap acceptance errors committed, five adjustment-to-stimuli errors optimally determined pass/fail outcomes in PwMS. Furthermore, with no adjustment to stimuli errors committed, committing any gap acceptance errors also optimally determined pass/fail outcomes in PwMS. Further research may focus on visual, cognitive, and/or motor impairments underlying adjustment-to-stimuli and gap acceptance errors for eventual development of rehabilitation strategies for PwMS.